2004
DOI: 10.4037/ajcc2004.13.6.469
|View full text |Cite
|
Sign up to set email alerts
|

Equivalence of the Bioimpedance and Thermodilution Methods in Measuring Cardiac Output in Hospitalized Patients With Advanced, Decompensated Chronic Heart Failure

Abstract: • Background An accurate and reliable noninvasive method for determining cardiac output/cardiac index would be valuable for patients with acutely decompensated advanced systolic heart failure.• Objectives To determine whether a correlation exists for cardiac output and index determined by using bioimpedance and thermodilution in patients with acutely decompensated complex heart failure and if differences between results with the 2 methods could be explained by the patients’ advanced condition.• Methods Cardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
38
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(40 citation statements)
references
References 19 publications
2
38
0
Order By: Relevance
“…While invasive angiography is the gold standard for haemodynamic assessment in cirrhosis, its applicability is limited in the majority of clinical settings. Impedance cardiography (ICG) is a non-invasive, operator-independent method of measuring thoracic fluid content (TFC) and haemodynamic parameters using changes in thoracic electrical impedance, and it has been applied and compared with invasive haemodynamic measurements mainly in heart failure and critical care patients (15)(16)(17). Although there is still limited experience with the use of ICG in cirrhotic patients (18)(19)(20)(21), a previous study showed good correlation between cardiac output and peripheral systemic resistance calculated by echocardiography and by ICG in patients with cirrhosis with and without ascites, concluding that ICG is a reliable method for assessing systemic haemodynamics in these patients (21).…”
Section: Introductionmentioning
confidence: 99%
“…While invasive angiography is the gold standard for haemodynamic assessment in cirrhosis, its applicability is limited in the majority of clinical settings. Impedance cardiography (ICG) is a non-invasive, operator-independent method of measuring thoracic fluid content (TFC) and haemodynamic parameters using changes in thoracic electrical impedance, and it has been applied and compared with invasive haemodynamic measurements mainly in heart failure and critical care patients (15)(16)(17). Although there is still limited experience with the use of ICG in cirrhotic patients (18)(19)(20)(21), a previous study showed good correlation between cardiac output and peripheral systemic resistance calculated by echocardiography and by ICG in patients with cirrhosis with and without ascites, concluding that ICG is a reliable method for assessing systemic haemodynamics in these patients (21).…”
Section: Introductionmentioning
confidence: 99%
“…ICG has been shown to be accurate and reproducible in studies comparing ICG with the thermodilution method using a pulmonary artery catheter. [1][2][3] ICG also allows measurement of electromechanical timing intervals, such as the systolic time ratio (STR), defined as the ratio of the preejection period (the time from the onset of QRS complex on the electrocardiogram to the opening of the aortic valve) divided by the LV ejection time (the time from the aortic valve opening to the aortic valve closing). Historically, systolic time intervals and ratios are well-established measures in the evaluation of LV performance but are no longer frequently used.…”
mentioning
confidence: 99%
“…In the last decades, many reports and reviews have been published on ICG with conflicting results and conclusions. Valuable ICG measurements have been reported (Woltjer et al 1997;Ono et al 2004;Sodolski & Kutarski 2007), with values comparable to those obtained by conventional methods such as thermodilution or Fick method (Woltjer et al 1996;Spiess et al 2001;Drazner et al 2002;Van De Water et al 2003;Albert et al 2004;Engoren & Barbee 2005), as well as inaccurate measurements with substantial variation between different algorythms (Woltjer et al 1997;de Waal et al 2008). Due to this, ICG as a useful clinical device has not yet gained wide acceptance (Donovan et al 1986;Wang et al 2006;de Waal et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Measurements by ICG were reported to be reliable as they correlate highly with clinical standard methods (Spiess et al 2001;Drazner et al 2002;Van De Water et al 2003;Albert et al 2004;Cotter et al 2004), however these results are debated by others (Drazner et al 2002;Sodolski & Kutarski 2007;Mathews & Singh 2008;Engoren & Barbee 2005;de Waal et al 2008). After more than 40 years of comparitive studies and improvements in hardware and software (Woltjer et al 1996;Ono et al 2004), the third generation ICG has now been introduced for clinical use, allowing measurement of multiple CV parameters.…”
Section: Introductionmentioning
confidence: 99%